Conceptual design of bio-composite chair and desk based on anthropometric data - Ali, Mahmood (2019)
This study is undertaken to design an anthropometrically enhanced Bio- Composite Chair and Desk to be used by students of Polytechnics in Malaysia . The Pugh total design method was used for this conceptual design and. There are 4 important stages in this study. First, evaluation of the anthropometric data (AD) of chair and desk currently used by polytechnics students was done. Second, generation design concepts of bio-composite desk and chair with and without anthropometric data using brainstorming, mind mapping and morphological chart was completed. Third, evaluation of the best design concept using weighted objectives method with inputs from Anthropometric data was completed. Finally, validation is carried out to validate the durability and comfortability of the new chair and desk under normal working conditions. Overall, the final proposed conceptual designed chair and desk provides an anthropometric interaction between the users and their workstation (chair and desk). This newly proposed chair and desk intends to enhance the teaching and learning process in the polytechnics and other institutions of higher learning.